Relação entre caracteres agronômicos na cultura de milho associado ao manejo de fungicida - Eggers, Henrique Schaf (2022)
Linear relationships help in the selection of characters of agronomic interest and can be useful in understanding the factors within the agronomic management of corn, such as cultivation environment, sowing time and phytosanitary management with fungicides. The objective of this work was to evaluate, through biometric models, the relationships between the production components and the morphological characters in the maize crop associated or not with the use of fungicides. Fourteen experiments were carried out in research areas located in Santa Maria, São Vicente do Sul and Frederico Westphalen - RS. Six corn hybrids (AG 9025 PRO3, AS 1730 PRO 3, P 3016 VYHR, MG 300 PW, DKB 230 PRO3 and SYN MAXIMUS VIP3) were evaluated, with and without fungicide applications, totaling twelve treatments. During the development of the culture, morphological and phenological characters and the measurement of grain mass were evaluated. For the evaluation of linear relationships, the path analysis methodology was used. The data referring to each environment were analyzed using the Microsoft Office Excel® application and the R software with 5% significance in the statistical tests. Cause and effect relationships were identified between the traits ear diameter, grain length, ear length, thousand-grain mass, percentage of deteriorated grains and leaf angle with a direct and indirect relationship with the increase in grain yield. The use of fungicides provided better conditions for the expression of morphological characters of maize plants, directly influencing productivity.